BUSINESS INTELLIGENCE FRAMEWORK FOR PERFORMANCE MEASUREMENT IN HIGHER EDUCATION STUDY PROGRAMS - Trisnawarman, Dedi; Imam, Muhammad Choirul (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2020)
Business Intelligence (BI) is an online application and realtime, needed by large and modern organizations to increase competitive advantage in the global competitive environment. Higher Education (HE) is a current organization that houses excellent resources, with the number of students reaching up to tens of thousands, thus requiring an application that can be used as a tool to achieve the organization's business goals. This study aims to build a BI model and framework aimed at developing decision-making applications for measuring the business performance of HE. The method used in this research is the BI development method which is derived from the software engineering development method and adapted to the Study Program Accreditation Instrument (IAPS) 4.0. The case study used is the Information Systems Study Program at Tarumanagara University. The BI development methods are: Business Case Assessment, Enterprise Infrastructure Evaluation, Project Planning, Project Requirements, Data Analysis, Prototyping, Meta Data Analysis, Database Design, ETL Design, Meta Data Design, ETL Development, Application Development, Data Mining, Meta Data Repository Development, Implementation, Release Evaluation. The results of this study are a development stage model and framework that can be used to build BI applications for study program performance measurement.ABSTRAK Business Intelligence (BI) adalah aplikasi daringdan terkini, dibutuhkan oleh organisasi besar dan modern untuk meningkatkan keunggulan kompetitif dalam persaingan global. Perguruan tinggi adalah organisasi saat ini yang memiliki sumber daya yang sangat baik, dengan jumlah mahasiswa mencapai puluhan ribu, sehingga membutuhkan aplikasi yang dapat digunakan sebagai alat untuk mencapai tujuan bisnis organisasi. Penelitian ini bertujuan untuk membangun model dan framework BI yang bertujuan untuk mengembangkan aplikasi pengambilan keputusan untuk mengukur kinerja bisnis PT. Metode yang digunakan dalam penelitian ini adalah metode pengembangan BI yang bersumber dari metode pengembangan rekayasa perangkat lunak dan disesuaikan dengan Instrumen Akreditasi Program Studi (IAPS) 4.0. Studi kasus yang digunakan adalah Program Studi Sistem Informasi Universitas Tarumanagara. Metode pengembangan BI adalah: Business Case Assessment, Enterprise Infrastructure Evaluation, Project Planning, Project Requirements, Data Analysis, Prototyping, Metadata Analysis, Database Design, ETL Design, Metadata Design, ETL Development, Application Development, Data Mining, Metadata Pengembangan Repositori, Implementasi, Evaluasi Rilis. Hasil dari penelitian ini berupa model tahapan pengembangan dan kerangka kerja yang dapat digunakan untuk membangun aplikasi BI untuk pengukuran kinerja program studi. Kata Kunci: Kerangka kerja Business Intelligence; Pengukuran Performa; Perguruan Tinggi